2014
DOI: 10.1096/fj.14-259770
|View full text |Cite
|
Sign up to set email alerts
|

Hind limb unloading, a model of spaceflight conditions, leads to decreased B lymphopoiesis similar to aging

Abstract: Within the bone marrow, the endosteal niche plays a crucial role in B-cell differentiation. Because spaceflight is associated with osteoporosis, we investigated whether changes in bone microstructure induced by a ground-based model of spaceflight, hind limb unloading (HU), could affect B lymphopoiesis. To this end, we analyzed both bone parameters and the frequency of early hematopoietic precursors and cells of the B lineage after 3, 6, 13, and 21 d of HU. We found that limb disuse leads to a decrease in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 55 publications
(69 reference statements)
4
35
0
Order By: Relevance
“…Here, IL-7Rα transcript expression was not different in the thymuses of 2G pups. Similarly, in another study, we showed that hind limb unloading, which simulates microgravity, decreased early B cell differentiation and that this reduction is not due to a decrease in IL-7Rα expression on murine pro-B cells4.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Here, IL-7Rα transcript expression was not different in the thymuses of 2G pups. Similarly, in another study, we showed that hind limb unloading, which simulates microgravity, decreased early B cell differentiation and that this reduction is not due to a decrease in IL-7Rα expression on murine pro-B cells4.…”
Section: Discussionsupporting
confidence: 63%
“…These data suggest that gravitational changes can modify B lymphopoiesis3. This hypothesis was recently confirmed using hind limb unloaded mice, a ground-based model of microgravity, where a decrease in B lymphopoiesis was observed as of the common lymphoid progenitor stage with a major block at the pro-B to pre-B cell transition4. Furthermore, we showed that a long-term spaceflight affects the use of immunoglobulin heavy chain variable gene segments (VH) subgroups5 and the expression of individual VH gene segments6 in response to an antigenic stimulation in adult P. waltl , thereby suggesting that these conditions could affect the V(D)J recombination machinery.…”
mentioning
confidence: 64%
“…; Lescale et al. ). Numerous studies indicate that body weight and body mass index are positively related to muscle, fat, and bone masses (Rosen and Bouxsein ; Muller et al.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in the maturation of granulocytic cells in the bone marrow of C57BL/6 mice were also reported after a 13 d spaceflight (8). Concerning lymphocyte development, it was shown that hindlimb unloading, a model frequently used to simulate spaceflight conditions, leads to decreased murine B lymphopoiesis, similar to aging (9). T lymphopoiesis was also shown to be sensitive to gravity changes, because reductions in CD4 + , CD8 + , and CD4 + CD8 + thymocyte populations were reported when murine fetal thymuses were cultured under clinorotation (10).…”
mentioning
confidence: 86%